Strategi Penyelesaian Pembiayaan Bermasalah di KSPPS BMT Bahtera Pekalongan - Afifah, Rahmatul; Hediati, Teti; Mubarok, Rizqon (el hisbah Journal of Islamic Economic Law, 2021)
Loss of Financing at KSPPS BMT Bahtera Pekalongan since 2021 has counted 75 customers with problems. Some Efforts have been made to deal with problematic financing at KSPPS BMT Bahtera Pekalongan. However, many customers are still experiencing financing problems. Therefore, the authors are interested in studying the Problem Financing Resolution Strategy. The approach used in this research is a qualitative approach, namely research procedures that produce descriptive data in the form of case studies, the type of research is in the form of case studies. The results of this study are the problematic financing factors, namely the presence of internal and external factors. There are 2 factors that cause financing. The first factor is the lack of good understanding of the customer's business and internal factors, namely the lack of customer financial evaluations and others. The second factor, namely the external factor of the negligence of members to pay installments or procrastination, the natural factors that are currently happening, namely the Covid-19 disaster and others. The strategy for resolving non-performing financing is notification by telephone or cellphone, giving billing letters, rescheduling, extending the term, extending the installment period, re-conditioning, rearranging, confiscation of guarantees and executing guarantees, and the last strategy is not to do anything. cooperation with problematic members for the long term, and must be careful in selecting prospective members of the BMT.